Unraveling the Activation Mechanism of the Potato Tuber ADP-glucose Pyrophosphorylase - Figueroa, Carlos Maria (2013)
ADP-glucose pyrophosphorylase regulates the synthesis of glycogen in bacteria and of starch in plants. The enzyme from plants is mainly activated by 3-phosphoglycerate and is a heterotetramer comprising two small and two large subunits. Here, we found that two highly conserved residues are critical for triggering the activation of the potato tuber ADP-glucose pyrophosphorylase, as shown by site-directed mutagenesis. Mutations in the small subunit, which bears the catalytic function in this potato tuber form, had a more dramatic effect on disrupting the allosteric activation than those introduced in the large subunit, which is mainly modulatory. Our results strongly agree with a model where the modified residues are located in loops responsible for triggering the allosteric activation signal for this enzyme, and the sensitivity to this activation correlates with the dynamics of these loops. In addition, previous biochemical data indicates that the triggering mechanism is widespread in the enzyme family, even though the activator and the quaternary structure are not conserved.